Financial literacy essentials - Tyson, Eric (Eric Kevin); Brown, Ray (Raymond); Carlson, Robert C., 1957-; Griswold, Robert S.; Munro, Margaret A. (--For dummies., 2025)
"The first step in becoming a better personal financial manager is understanding the pillars of personal finance. Financial Literacy Essentials For Dummies is your cheat sheet on understanding how to better manage your finances. Distilled down to the essentials, this book makes it easy for anyone to learn the basics of managing money. You won't be able to escape life's many expenses, but with this book, you can get a grip on smart spending, saving, investing, and beyond. Start by creating a realistic budget for your situation and make a plan for achieving your goals"--